# Solve for h h(-7)=2/3*(-7)+1

h(-7)=23⋅(-7)+1
Simplify.
Multiply 23(-7).
Combine 23 and -7.
h(-7)=2⋅-73+1
Multiply 2 by -7.
h(-7)=-143+1
h(-7)=-143+1
Move the negative in front of the fraction.
h(-7)=-143+1
Write 1 as a fraction with a common denominator.
h(-7)=-143+33
Combine the numerators over the common denominator.
h(-7)=-14+33
Add -14 and 3.
h(-7)=-113
h(-7)=-113
Divide each term by -7 and simplify.
Divide each term in h(-7)=-113 by -7.
h(-7)-7=-113-7
Cancel the common factor of -7.
Cancel the common factor.
h⋅-7-7=-113-7
Divide h by 1.
h=-113-7
h=-113-7
Simplify -113-7.
Multiply the numerator by the reciprocal of the denominator.
h=-113⋅1-7
Move the negative in front of the fraction.
h=-113⋅1-7
Move the negative in front of the fraction.
h=-113(-17)
Multiply -113(-17).
Multiply -1 by -1.
h=1(113)17
Multiply 113 by 1.
h=113⋅17
Multiply 113 and 17.
h=113⋅7
Multiply 3 by 7.
h=1121
h=1121
h=1121
h=1121
The result can be shown in multiple forms.
Exact Form:
h=1121
Decimal Form:
h=0.523809‾
Solve for h h(-7)=2/3*(-7)+1

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top